Anatomical Variations of the Sinonasal Area and Their Clinical Impact on Sinus Pathology: A Systematic Review - Anna-Maria Papadopoulou; Nikolaos Bakogiannis; Ioanna Skrapari; Chris Bakoyiannis (International Archives of Otorhinolaryngology, 2022)
Introduction Anatomical variations of the nasal cavity and of the paranasal sinuses are frequently encountered and play an important role in dysfunctional drainage of sinuses. However, it is not clear in the literature whether they predispose to sinus pathology. Objectives The aim of the present review is to summarize the understanding of the association between anatomical variations of the sinonasal area and sinus pathology. Data Synthesis The present review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. We performed a thorough research on PubMed from October 2004 until May 2020 by using the search terms paranasal sinus anatomical variations and sinus disease, sinusitis, and mucosal disease. Thirty studies were eligible and were included in the analysis. Overall, the studies encompassed a total of 6,999 patients included in the present review. In many studies, it has been statistically established that certain anatomical variations increase the risk of sinus disease. On the other hand, the rest of the collected studies failed to show any statistically significant correlation between anatomical variants and sinus pathology. Conclusion The present study highlights the possible correlation between some anatomical variations of the sinonasal area and pathologies of the paranasal sinuses. Careful assessment and computed tomography (CT) in patients with chronic rhinosinusitis is needed, especially in those undergoing endoscopic surgery, to identify and treat anatomical variations in the paranasal sinuses that may be correlated with rhinosinusitis. Due to contradictory results in the literature, further research is needed to elucidate the effects of anatomical variants of the sinonasal area.